Latin American social work challenges against the barbarization of capitalism - Dulcich Piccolo, Ramiro Marcos (2025)
The text proposes to reflect on the historical determinations of contemporary capitalism in our America, as a basis for the debate on the challenges of social work in the region. For contradictions of its mature phase, capitalism reproduces at the cost of increasing levels of social and environmental destructiveness, affirming in regressive and controlling trends that dehumanize the social being. The return of neoliberal hegemony in our America unleashed a process of dehumanization, of barbarization of social life, which is rooted by the destruction of the living workforce through unemployment. This context threatens the consolidation of critical professional projects in social work. Restrictions in relative autonomy in their work, precariousness of contracts, scarcity of resources and instability demarcate occupational spaces. The re-ascense of social movements can contribute to the formulation of responses to redefine the margins of professional practice.